Analysis of the interaction between rubber polymer and carbon black surfaces by efficient removal of physisorbed polymer from carbon-rubber composites. (April 2016) - Hoshikawa, Yasuto; An, Baigang; Kashihara, Susumu; Ishii, Takafumi; Ando, Mariko; Fujisawa, Syuji; Hayakawa, Koutarou; Hamatani, Satoshi; Yamada, Hiroshi; Kyotani, Takashi
Abstract: The purpose of the present study is to provide insight into the structure of "bound rubber", which is responsible for the reinforcing effect of carbon black (CB) in a rubber composite. When styrene-butadiene rubber (SBR)-CB composites were treated with toluene at a high temperature (150 °C) in an autoclave (AC) vessel, it was found that the AC treatment extracted a much larger amount of physisorbed rubber than the conventional Soxhlet extraction. Moreover, the pulsed 1 H NMR technique reveals that the AC treatment can extract almost all of "loosely bound rubber" but leave "tightly bound rubber". An attempt was then made to correlate the amount of tightly bound rubber with the carbon surface chemistry in CB. As a result, a good linear relationship was found between the amount of tightly bound rubber and the hydrogen content of CB among four SBR composites with different types of CBs. Based on the above linear relationship, the origin of the tightly bound rubber is discussed in terms of the nature of the interaction (chemical and physical) between the rubber polymer chains and the CB surface.